(untitled) (Journal of Hama University, 2022)
The purpose of this study was to investigate the effect of dentin surface treatment with aluminum oxide air abrasion and Er:YAG laser on tensile bond strength of metal crowns that luted with resin modified glass ionomer cement (RMGIC) in the teeth with reduced crown height, where preparation geometry did not provide optimal retention form. A 30 human premolars were prepared to receive metal crowns and were divided into three groups for tensile bond strength testing Group A: Surface treatment with Er:YAG laser, Group B: Surface treatment with 50 μm aluminum oxide air abrasion, Group C: Untreated dentin as negative control. all abutments were cemented with RMGIC cement. A pull-off test was applied until separation. Data were analysed to compare the correlation of the three groups using one-way ANOVA and Shapiro-Wilk test (p ≤ 0.05). The mean retentive values in Newton were as follows: the laser group, 610.2±32.6; the air abrasion group, 734.3 ± 12.8 and the conrol group, 599.7 ± 36. One-way analysis of variance showed statistically significant difference among/within the groups (p < 0.001). Conclusion: Dentin surface treatment with Air Abrasion significantly improved the tensile bond strength of luting RMGIC compared to Er:YAG lased and untreated dentin.